Religious Coexistence in Ottoman Palestine: A Socio-Historical Study - Aybey, Beyza; Mohd Bakri, Mohamad Fikri (Journal Al-Muqaddimah, 2026)
This study analyzes religious coexistence in Bayt al-Maqdis during the Ottoman rule, focusing on the millet system that regulated religious and social life. The millet system granted autonomy to religious communities but faced challenges such as sectarian tensions among Christian communities and foreign intervention, particularly from Russia and France. These tensions, along with the influence of the Zionist movement on the Jewish community, revealed the system’s weaknesses in managing sectarian differences and external influences. The study also examines how Tanzimat reforms transformed the administrative structure and how the millet system adapted to these changes, particularly through the establishment of municipal councils. Overall, the Ottoman millet system provided a space for religious coexistence but was vulnerable to tensions and social changes that challenged political and social stability.